KECENDERUNGAN TEOLOGI MATURIDIYAH SAMARKAND - Zuhri, Amat (RELIGIA, 2010)
Al-Maturidi – a prominent figure of Maturidiyah of Samarkand branch – is Abu Hanifah’s follower who uses ratio much in religious view including in theological thought. In fact, Maturidiyah of Samarkand’s thought is closer to Mu’tazilah’s one because they use ratio in the same way, but Maturidiyah of Samarkand is still grouped into Ahl al- Sunnah wa al-Jama’ah group, which is a derivation of Asy’ariyah view, even though Asy’ariyah does not use ratio much in theological thought.